Band dispersion in the deep 1s core level ofgraphene - Lizzit, Silvano (2010)
It is generally assumed that electrons in deep atomic core states are highly localized and do not participate in the bonding of molecules and solids. This implies well-defined core-level binding energies and the absence of any splitting and band-like dispersion, a fact that is exploited in several powerful experimental techniques, such as X-ray photoemission spectroscopy. Violations of this assumption have been found for only a few small molecules in the gas phase such as C 2 H 2 or N 2 with much stronger bonding and shorter bonding distances than present in solids. Here we report the observation of a sizeable band-like dispersion of the C 1s core level in graphene, a single-layer honeycomb net of carbon atoms that is attracting considerable attention at present in the scientific community. The dispersion is observed as an emission-angle-dependent binding-energy modulation and it is shown that under appropriate conditions only the bonding or antibonding states can be observed. A very similar dispersion is also found by ab initio calculations.